2018
DOI: 10.1002/bdm.2097
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in financial decision making:The benefits of more experience and less negative emotions

Abstract: The emerging literature on aging and decision making posits that decision‐making competence changes with age, as a result of age differences in various cognitive and noncognitive individual‐differences characteristics. In a national life‐span sample from the United Kingdom (N = 926), we examined age differences in financial decisions, including performance measures of sunk cost and credit card repayment decisions, and self‐report measures of money management and financial decision outcomes. Participants also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
63
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 96 publications
14
63
1
5
Order By: Relevance
“…It is necessary to take into account the motivational profile to present an appropriate argument. Indeed, when a decision is made in a known situation, older persons will easily rely on experience [70]. However, when decisions involve new situations, the arguments presented will be essential.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to take into account the motivational profile to present an appropriate argument. Indeed, when a decision is made in a known situation, older persons will easily rely on experience [70]. However, when decisions involve new situations, the arguments presented will be essential.…”
Section: Discussionmentioning
confidence: 99%
“…Katona (1975) discussed the origin of the credit problem, and Azma et al (2019) highlighted psychological and behavioral factors. Following this view, Eberhardt et al (2019) and Vitt (2004) identified that consumers' financial decisions may reflect their psychological and social values.…”
Section: Theoretical Basismentioning
confidence: 99%
“…The third cluster (in blue) forms a network of terms about the individual, such as human, gender, aged, adult, adolescent, or quality of life. The use of financial incentives to promote education and employment [98], in addition to a pertinent pedagogy for entrepreneurship education, must consolidate small businesses and business development [99,100]. Financial education has an important role in business success.…”
Section: Introductionmentioning
confidence: 99%